Comportamiento agronómico y valor nutricional de la asociación de cuatro variedades de pastos (Panicum máximum Jacq), con la leguminosa matarratón (Gliricidia sepium), en el colegio Jaime del Hierro en Santa María del Toachi. - Vela Espín, Lucio Enin (2015)
The research presented here was performed at the Colegio Jaime del Hierro in Santa María de el Toachi, Santo Domingo province of the Tsachilas, study which aimed at general: evaluate the agronomic performance and nutritional value of the Association's four varieties of grasses (Panicum maximum Jacq) with the legume gliricidia (Gliricidia sepium) in the Colegio Jaime del Hierro in Santa María de el Toachi andspecific: determine the performance of each of the varieties of Panicum green forage production maximum Jacq; Learn about the production of forage biomass of the legume gliricidia (Gliricidia sepium); set the nutritional value of the Association of the varieties of Panicum maximum Jacq with the legume gliricidia (Gliricidia sepium), using a complete block to random (DBCA) design in array factor, with four associations, three States of maturity and three replications. The most relevant results we find in the Savoy Association common gliricidia, same that obtains the greatest numbers with 5.01 branches, grass forage production in the variable number of branches reached the highest values in this same partnership with 809,25 g m2, whereas in the legume forage production was obtained in Savoy Tanzania gliricidia 98,08 g m2. The most appropriate age for the cut of grasses was achieved at 90 days where the values were obtained higher in number of branches, production of forage grass and fodder from the legume with 5.19 branches, 937,38 g m2 and 103,31 m2 g. Bromatologic analysis of study associations, dwarf Savoy gliricidia 90 days achieved the highest levels of protein with 16.70%.